Are the functional diversity terms functional? The hindrances of functional diversity understanding in the Brazilian scientific community - Bastos‐Pereira, Rafaela; Chagas, Tássia Rayane Ferreira; Carvalho, Débora Reis; Rabello, Ananza Mara; Beiroz, Wallace; Tavares, Karla Palmieri; Lima, Karen Cristina Braga; Rabelo, Lucas Mendes; Valenzuela, Silvia; Correa, César M. A.; Pompeu, Paulo Santos; Ribas, Carla Rodrigues (Ecological research, 2022)
Interest in functional diversity has grown in recent years, indicating that knowledge on ecosystem functions gain importance. However, the incongruent use of terms may lead to misunderstandings and incomparable results. We aimed to review terms used in functional diversity among the Brazilian scientific community to identify if there is a lack of consensus in the terminology used. We applied online surveys to assess how these terms have been used by the Brazilian academics and searched for their definitions in the scientific literature. The definition of “ecological function” by Brazilian academics is like that of the niche, but we only found two articles defining such a term in the literature. Thus, it seems that “ecosystem function” is a more commonly used term outside of Brazil. The definition of “guilds” coincided with that used in the literature, although we still observed a lack of consensus in the latter. For “traits,” “functional group,” and “functional diversity” concepts, we found some discrepancy between the literature and questionnaires. These inconsistencies can be related to the use of different organizational levels for the definition of traits and to the practice of replacing species with functional groups in standard taxonomic diversity metrics, considering them as measurements of functional diversity. The adoption of cohesive terminology is crucial to ensure the comparability of scientific results in the scientific literature. However, finding a consensus in ecology represents a hard task; therefore, we encourage that, at least, researchers make clear which key concepts they adopted in their research to avoid misunderstandings. We investigated through online surveys if there was consistency between the terminology used by Brazilian researchers regarding functional diversity. We found consistent results for “Ecological function” and “Guild” concepts, although for “Traits”, “Functional group” and “Functional diversity” there were some discrepancy between literature and researchers definitions. The use of different organizational levels and the practice of running usual taxonomic diversity metrics replacing species by functional groups as an approach to functional diversity may be the cause of such inconsistencies.